Bullying di desantren: Interaksi Tasawuf dan Teori Pengembangan Fitrah dalam Pendidikan Islam - Nurul Hikmah Sofyan (Journal of Islamic Studies and Humanities, 2019)
This study aims to explain the bullies and the victims of bullying based on Islamic psychology perspective that uses tasawuf approach (sufistic psychology) through documentation as data collecting technique. In more detail, this research is focused on strengthening the theory of the development of student’s nature as the main vision of Islamic education. Islamic education requires an explanation of sufistic psychology which does have a primary concern in developing all potential fitrah in human. Sufistic Psychology of Imam Al-Gazali summarized in Kimiyāu Al-Sa’ādah is used by researcher to read and understand the behavior of bullies and victims. Bullies are understood as individuals who have strong dominance in the power of their gaḍab so they can easily attack victims. Meanwhile, victims are understood as individuals who do not use the power of gaḍab effectively. Victims are lack of lust so that there is no courage and ability to defend themselves when faced with bullying toward them. Responding to such problem, sufistic psychology requires control over the actualization of gaḍab and syahwat without intending to kill these two potentials.